G343(P) Development of a mobile application to facilitate in-situ simulation delivery. (24th May 2017) - Edelman, J; Bennett, T
Abstract : Aims: Simulation is being used to teach multi-professional teams in a range of environments. Moving simulation from the controlled simulation suite to the ward and prehospital environment presents a challenge for educators who need the scenarios at their fingertips. With the ongoing development of new simulation material across the world, collating this material becomes challenging and inefficient. It is recognised that there is currently no simple way of sharing good quality simulation educational material among educators. As mobile technology becomes ever more accessible, we present a mobile application which enables simulation material to be collated, shared and delivered from a single device. Methods: We have developed a mobile app for iOS devices which is available for free on the Apple App Store. The app contains a range of locally stored paediatric simulation scenarios in a user-friendly interface, including media such as videos/images. These can be used by educators to facilitate simulations in any environment. The application also utelises a server-based back-end, which enables new simulations to be submitted by users and uploaded to the app in real-time, allowing the bank of scenarios to grow and to be easily shared. In addition, the appication also collates useful weblinks to organisations, moulage tips and other information to enhance simulation delivery. Results: The application was released in the Apple App Store in December 2016 and we are currently collecting data on its download and usage worldwide. Feedback on the application has been very positive, and it has already been awarded regional and national awards in the UK. We are currently conducting a pilot study in the South of England to evaluate the impact our application has on the ease of simulation delivery and the improvement of access to new simulation material. This data analysis will be completed in early 2017. Conclusion: We believe that our application will allow simulation educators to have access to an ever-expanding bank of scenarios which can be delivered with ease in multiple environments. By embracing a paperless approach to simulation delivery we can improve the way in which in-situ simulation is used and will allow this valuable teaching modality to be utelised more widely.